Participatory assessment of biodiversity conservation in community forestry in Nepal - Acharya, K.P.; Goutam, K.R.; Acharya, B.K.; Gautam, G. (Banko Janakari, 2007)
The Community Forestry has been the most effective means of managing common forest resources in Nepal. Besides rehabilitating degraded hills, improving environment and contributing to the rural livelihoods, community forestry is claimed to be a major means of biodiversity conservation. It is also argued that the prevalent approach of community forest management threats to the conservation of biodiversity. This paper is based on the findings from two community forest user groups from Central Nepal and argues that the users’ innovative practices of active forest management favor biodiversity conservation. The study has documented users’ innovations to conserve biodiversity in community managed forests. Key words: Nepal, community forestry, biodiversity conservation and livelihoods Banko Janakari Vol.16(1) 2006 pp46-56